The impact of multiple single day blood pressure readings on cardiovascular risk estimation: The Atherosclerosis Risk in Communities study. (September 2016) - Ogunwale, Abayomi N; Morrison, Alanna C; Sun, Wensheng; Dodge, Rhiannon C; Virani, Salim S; Taylor, Addison; Gottesman, Rebecca F; Yang, Eric; Wei, Peng; McEvoy, John W; Heiss, Gerardo; Boerwinkle, Eric; et al.
Aims: The aim of this study was to determine the magnitude of change in estimated cardiovascular disease risk when multiple same day blood pressure measurements are used in estimating coronary heart disease, heart failure and stroke risks. Methods and results: Black and White participants, N = 11, 129, enrolled in the Atherosclerosis Risk in Communities study (mean age 53.9 ± 5.7 (SD) years) were included. Each participant had three sitting, five supine, and six standing blood pressure measures during one day. Main outcome measures were changes in estimated coronary heart disease, heart failure and stroke risk when using the different blood pressure measures. Mean sitting, standing and supine systolic blood pressure values of the study population were 120.8 ± 18.6, 124.9 ± 20 and 124.7 ± 19.6 mmHg, respectively. The substitution of the second sitting systolic blood pressure with the third sitting systolic blood pressure (taken ∼5 min later) in two separate coronary heart disease risk models reclassified 3.3% to 5.1% of study participants. Similar substitutions for heart failure and stroke risk prediction models led to reclassification of 1.9% and 2.7% of participants respectively. When mean sitting systolic blood pressure was replaced with mean standing systolic blood pressure 5.4% to 11.6% of the participants were reclassified. Maximum upward and downward change in an individual's estimated risk was 31% and 26% respectively. Conclusions: Estimated risks of coronary heart disease, heart failure, and stroke for an individual can change significantly within a day due to changes in systolic blood pressure. Given recommendations to use estimated risk for therapeutic decisions, our study has implications for the use of a single systolic blood pressure in cardiovascular risk estimation.